2017
DOI: 10.18632/oncotarget.18485
|View full text |Cite
|
Sign up to set email alerts
|

Changes of peripheral lymphocyte subsets and cytokine environment during aging and deteriorating gastrointestinal tract health status

Abstract: Human immune senescence accompanies with the physical and physiological frailty. The functional change and shift of NK, NKT and T cell subsets by aging have been widely studied. However, it remains largely unclear how the aging and disease conditions affect the distribution of lymphocytes. In the present study, 233 subjects with age range from 20 to 87 year old, including healthy people, people with chronic gastrointestinal tract disease or cancers were investigated. We found that the proportion of NK cells, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…The age of the participants is categorized into three age groups—young adults (1 = aged 20–35 years), middle-aged adults (2 = aged 36–55 years), and older adults (3 = aged 56 years and older). This categorization of age groups was adopted from the previous studies which investigated various relevant topics including health behavior change and aging aspects ( Petry, 2002 ; Palmiero et al, 2017 ; Wang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of the participants is categorized into three age groups—young adults (1 = aged 20–35 years), middle-aged adults (2 = aged 36–55 years), and older adults (3 = aged 56 years and older). This categorization of age groups was adopted from the previous studies which investigated various relevant topics including health behavior change and aging aspects ( Petry, 2002 ; Palmiero et al, 2017 ; Wang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Age groups should be analyzed in regard to whether young adults (i.e., 20–35 years) differ from middle-aged adults (i.e., 36–55 years) and the aging older adults that included both young-old- and oldest-old adults (i.e., older than 56 years). This grouping approach was chosen by previous study related to health behavior change ( Petry, 2002 ; Ziegelmann et al, 2006 ), and some studies which are related to the aspects of aging ( Palmiero et al, 2017 ; Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Arango et al evaluated lymphocyte subpopulations in Cuban cancer patients and found that with increasing age, there is a tendency for a decrease in T, B, and NK lymphocyte populations, and patients with solid tumors showed the lowest values (17). Wang et al demonstrate that age is one of the variables that most in uences immunosenescence and they conclude that T cells, NK cells, and NKT cells are gradually affected in cancer (23).…”
Section: Resultsmentioning
confidence: 99%
“…As the central executors to lyse neoplastic cells, T-cell incapacities are caused by external inhibition and internal abnormal expressions of T-cell clonal receptors, co-stimulators, and immunosenescence. 16,17 Whereas cellular inhibition of T-cell tumour immunity involves Treg activity, 18 co-inhibitory checkpoints are mediated by PD-1 on the T-cell with PD-L1 on tumour cell, and immunosuppression under various conditions such as transformation of neoplastic cells and nosocomial infection. Blocking the interaction of PD-1 with PD-L1 by gene knockout or inhibitory antibodies reverses T-cell dysfunction and improves survival from late-stage cancer or sepsis.…”
Section: The T-cell Neg Ative Reg Ul Atory Checkp Ointsmentioning
confidence: 99%